The Toxic Effects of Polychemotherapy onto the Liver Are Accelerated by the Upregulated MDR of Lymphosarcoma. (29th November 2012) - Sen'kova, Alexandra V.; Mironova, Nadezhda L.; Patutina, Olga A.; Ageeva, Tatyana A.; Zenkova, Marina A.
Abstract : Antitumor therapy of hematological malignancies is impeded due to the high toxicity of polychemotherapy toward liver and increasing multiple drug resistance (MDR) of tumor cells under the pressure of polychemotherapy. These two problems can augment each other and significantly reduce the efficiency of antineoplastic therapy. We studied the combined effect of polychemotherapy and upregulated MDR of lymphosarcoma RLS40 onto the liver of experimental mice using two treatment schemes. Scheme 1 is artificial: the tumor was subjected to four courses of polychemotherapy while the liver of the tumor-bearing mice was exposed to only one. This was achieved by threefold tumor retransplantation taken from animals subjected to chemotherapy into intact animals. Scheme 2 displays "real-life" status of patients with MDR malignancies: both the tumor and the liver of tumor-bearing mice were subjected to three sequential courses of polychemotherapy. Our data show that the strengthening of MDR phenotype of RLS40 under polychemotherapy and toxic pressure of polychemotherapy itself has a synergistic damaging effect on the liver that is expressed in the accumulation of destructive changes in the liver tissue, the reduction of the regeneration capacity of the liver, and increasing of Pgp expression on the surface of hepatocytes.